Liver-derived ketone bodies are necessary for food anticipation - Chavan, Rohit; Feillet, Céline; Costa, Sara S. Fonseca; Delorme, James E.; Okabe, Takashi; Ripperger, Jürgen A.; Albrecht, Urs (Nature communications, 2016)
The circadian system has endowed animals with the ability to anticipate recurring food availability at particular times of day. As daily food anticipation (FA) is independent of the suprachiasmatic nuclei, the central pacemaker of the circadian system, questions arise of where FA signals originate and what role components of the circadian clock might play. Here we show that liver-specific deletion of Per2 in mice abolishes FA, an effect that is rescued by viral overexpression of Per2 in the liver. RNA sequencing indicates that Per2 regulates β-hydroxybutyrate (βOHB) production to induce FA leading to the conclusion that liver Per2 is important for this process. Unexpectedly, we show that FA originates in the liver and not in the brain. However, manifestation of FA involves processing of the liver-derived βOHB signal in the brain, indicating that the food-entrainable oscillator is not located in a single tissue but is of systemic nature. Food anticipation is thought to be initiated by the central clock in the brain. Here the authors show that the peripheral organs initiate this process by showing that liver-specific deletion of Per2 can inhibit food anticipation by interfering with ß-hydroxybutyrate production and its subsequent processing in the brain.